To chop or not to chop? Tackling shrub encroachment by roller-chopping preserves woody plant diversity and composition in a dry subtropical forest - Rejžek, Martin; Coria, Rubén Darío; Kunst, Carlos Roberto; Svátek, Martin; Kvasnica, Jakub; Navall, Jorge Marcelo; Ledesma, Roxana Ramona; Gomez, Adriana Teresita; Matula, Radim (2018)
Shrub encroachment is a frequently observed phenomenon in the arid and semi-arid biomes. In the dry forests of the Argentine Chaco ecoregion that are affected by shrub encroachment, the growing demand for grazing areas has led to the creation of a silvopastoral system. Under the Chaco silvopastoral system, a commonly used treatment to disrupt the excessive shrub layer and promote the growth of grasses is roller-chopping by a tractor-pulled iron drum. While previous studies evaluating the effects of roller-chopping on diversity have focused mostly on the herbaceous stratum as the primary source of forage, much less is known about the effects of roller-chopping on woody plants. To fill this gap, we measured woody plants of the shrub layer in a low-intensity roller-chopping experiment in northern Argentina after applying different frequencies of roller-chopping in a semi-arid Chaco forest area with a well-developed shrub layer. Data were collected in an experiment in which 3 different roller-chopping treatments were applied: a single two-pass roller-chopping in the summer of 2006/2007 (RCh1); a one-pass roller-chopping in the summer of 2006/2007, repeated in the summer of 2014/2015 (RCh2); and no treatment (Control). In each treatment, 16 circular, randomly placed plots with a radius of 9 m were sampled, and all woody plants in the shrub layer with a diameter ≥10 mm at the base were recorded. The diversity was analysed using profiles of alpha and beta diversity and by calculating the average distance from an individual circular plot to the treatment group centroid defined in the principal coordinate space. In total, 26 species of woody plants were recorded, of which 24 were found in Control, 22 in RCh1, and 23 in RCh2. Although the alpha diversity differed only slightly among the treatments, the beta diversity of the roller-chopped treatment areas was generally higher than that of the untreated plots. The species composition of the roller-chopped plots differed little from that of the control plots. Our study revealed little overall effect of roller-chopping on the species diversity and composition of woody plants. The transformation of the Chaco forest degraded by shrub encroachment to a silvopastoral system by roller-chopping is changing the structure of the forest but to a large extent has retained the presence and the relative abundance of woody plant species. We conclude that roller-chopping is a good management tool to reduce woody plant encroachment and create a silvopastoral system while preserving ecosystem functions.